13-Month-Olds' Understanding of Social Interactions. (March 2015) - Choi, You-jung; Luo, Yuyan
In the present research, we investigated how 13-month-olds use their emergent theory-of-mind understanding (i.e., understanding about other people's mental states, such as their intentions, perceptions, and beliefs) and social-evaluation skills to make sense of social interactions. The infants watched three puppets (A, B, and C) interact. The results showed that after seeing Agents A and B interact in a positive manner, infants expected them to continue doing so, even after they saw B hit another agent, C, while A was absent. When A was present to witness B's harmful action, however, infants expected A to change his or her behavior and ignore B. Therefore, infants seemed to consider A's perspectives when predicting A's actions. Furthermore, if B accidentally hit C when A was present, infants seemed to accept that A could interact or not interact with B, which suggests that they had taken into account B's intention in their interpretations of the agents' interactions.